2021
DOI: 10.1021/acsanm.1c00458
|View full text |Cite
|
Sign up to set email alerts
|

Z-Scheme Bi/Bi2O2CO3/Layered Double-Hydroxide Nanosheet Heterojunctions for Photocatalytic CO2 Reduction under Visible Light

Abstract: A Z-scheme Bi2O2CO3/Bi/NiAl-LDH (BBOC/LDH) nanosheet heterojunction was fabricated by a hydrothermal method. The BBOC/LDH composites exhibited superior performance for photocatalytic CO2 reduction. A maximum yield of CH4 with the value of 56.64 μmol/gcat was achieved on 20%BBOC/LDH composite, which was 3.9-fold higher than pure LDH. The larger specific surface area, and the efficient separation of photoexcited electrons and holes attributed to the metal Bi SPR effect and Z-scheme heterojunction, enhanced the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 68 publications
(27 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…This process can significantly reduce the charge carrier combination rate and achieve higher photocatalytic efficiency. The process of photoreduction of CO 2 can be described by the following formulas: …”
Section: Results and Discussionmentioning
confidence: 99%
“…This process can significantly reduce the charge carrier combination rate and achieve higher photocatalytic efficiency. The process of photoreduction of CO 2 can be described by the following formulas: …”
Section: Results and Discussionmentioning
confidence: 99%
“…The XRD patterns of the synthesized CeO . 29 As shown in Fig. 3d, the high-resolution spectrum of Ce 3d shows three sets of spin-orbit dipole peaks with CeO 2 , where the peaks at 884.5 eV and 902.9 eV can be ascribed to Ce 3+ , which can demonstrate the presence of oxygen vacancies in both CeO 2 and CB-15.…”
Section: Characteristicsmentioning
confidence: 79%
“…Various metal oxides, pnictides, and chalcogenides have been attached onto g-C 3 N 4 in order to fabricate direct Z-scheme heterojunction photocatalyst composites. Oxides such as WO 3 and TiO 2 , Ni and Co-based phosphides, and sulfides such as Bi 2 S 3 and SnS 2 have been successfully conjugated with g-C 3 N 4 to make direct Z-scheme heterojunctions. Many g-C 3 N 4 based direct Z-schemes have been synthesized for specifically employing in photocatalytic CO 2 reduction reactions. A composite consisting of WO 3 /g-C 3 N 4 was designed by Ohno and co-workers for photocatalytic CO 2 reduction application, which showed significantly better photocatalytic performance as compared to the bare semiconductor catalysts . A double beam photoacoustic spectroscopy revealed that the heterojunction followed a direct Z-scheme recombination route.…”
Section: Photoreduction Reaction Of Co2 Over G-c3n4 Composite-type He...mentioning
confidence: 99%
“…The composite system showed enhancement of photocatalytic CO 2 reduction capability in terms of both reactivity and selectivity . For quite a long time, bismuth-based photocatalysts have been used in various photochemical transformations, and the CO 2 reduction reaction is no exception. , Chalcogenides, oxyhalides, and mixed metal oxides of bismuth have been used generously to fabricate direct Z-scheme heterojunctions with g-C 3 N 4 . Two-dimensional ultrathin nanosheets of BiVO 4 have been effectively coupled with 2D g-C 3 N 4 to construct a heterojunction related to the direct Z-scheme .…”
Section: Photoreduction Reaction Of Co2 Over G-c3n4 Composite-type He...mentioning
confidence: 99%